Enabling stress determination on alkaline textured silicon using Raman spectroscopy. (September 2017) - Büchler, Andreas; Beinert, Andreas; Kluska, Sven; Haueisen, Viola; Romer, Pascal; Heinz, Friedemann D.; Glatthaar, Markus; Schubert, Martin C.
Abstract: Confocal micro-Raman spectroscopy allows for spatially resolved measurements of the phonon energy in silicon, which is correlated to mechanical stress. Mechanical stress is a tensorial quantity. For the confocal measurement geometry and certain crystal orientations approximations have been derived in the past which correlate the shift of the Raman frequency to a scalar stress value. For optimization of mono-crystalline solar cell manufacturing steps the determination of induced mechanical stress from the top view perspective is desirable. However, this method is so far restricted to planar wafers or cross sections. we find that the anti-reflection surface texture strongly affects the measurement result. To enable quantitative stress determination of alkaline textured silicon a suited measurement procedure is investigated using 3-point bended solar cell segments. Preceding elasticity test revealed Young's module and allowed a prediction of maximum stress values for any bending radius. We propose a measurement procedure which yields an observable shift of the Raman frequency proportional to the induced stress. We state the requirements for determination of a calibration factor to quantify stress on any alkaline textured solar cell. Adapting the conversion factors allows calibrated measurements for textures with different average pyramid heights. By varying the numerical aperture and the focus setting even changes of the induced stress within the texture pyramids are resolved.